Organisational Elements Controlling the Labour Efficiency in Sri Lankan Road Construction Projects: Engineers’ Perspective - Manoharan, Kesavan; Dissanayake, Pujitha; Pathirana, Chintha; Deegahawature, Dharsana; Silva, Renuka (International Journal of Sustainable Construction Engineering and Technology, 2023)
Labour efficiency is crucial for a construction firm’s long-term viability. According to recent studies, modernising organisational and administrative procedures is essential to improving labour efficiency in many developing countries, including Sri Lanka. The perspectives of construction engineers play a key role in strengthening organisational policies and management practices in the construction industry. As a result, based on the viewpoint of construction engineers, this study aims to identify the critical organisational elements that highly influence labour efficiency in Sri Lankan road construction projects. The elements/factors were qualitatively discovered after a thorough literature review. Then, a questionnaire survey was conducted among construction engineers employed by 31 Sri Lankan road construction contractors. The Relative Importance Index (RII) method was used to quantify each element’s level of influence on labour efficiency. Based on RII values, 33 organisational elements were determined as critical, where lack of communication and cooperation between the parties, delay in salary payment and lack of labour training facilities were determined as the top three ranking elements in the list. The validity and reliability of the results were confirmed by additional statistical tests. Using problem-based communication strategies, industry consultations were conducted among construction experts to determine the necessary future measures from relevant authorities based on the identified critical elements. These consultation outcomes suggest that the organisational policies of construction enterprises currently in place addressing financial procedures, communication strategies, resource management, performance management and training development practices must be improved in light of the new normal conditions facing the industry. The study findings might help to close the gap between management/organisational policies and workforce practices. Despite the fact that the study findings are limited to the Sri Lankan road construction industry, some of them could be used to address comparable issues in other developing nations.